CASE STUDY ABOUT LOW MOTIVATION TO LEARN SBDP IN CLASS V STUDENTS OF AL-KHAIRAT SOLONSA SD IN THE PANDEMIC TIME COVID 19 - Sulviana Sulviana; Yun Ratna Lagandesa (Jurnal Dikdas, 2021)
The focus of this research is the Low SBdP Learning Motivation in Class V SD Al-Khairat Solonsa during the Covid 19 Pandemic. This study aims to determine the factors causing the low SBdP Learning Motivation in Class V SD Al-Khairat Solonsa Students during the Covid Pandemic. 19. The subjects of this study were 19 grade students of SD Al-Khairat Solonsa. Data collection techniques in this study using observation, questionnaires, interviews and documentation with the technique "Descriptive Analysis" with the formula. Of the 19 students who became respondents, there were 84.21% who had high learning motivation and 3 students or 15.78% who had low learning motivation. The low SBdP learning motivation is due to 2 factors, namely internal factors including physical and psychological factors, while external factors are influenced by family factors, school factors and community factors.